EVOO polyphenols can relieve autophagy dysregulation in Alzheimer's disease: Molecular and cell biology/neurodegeneration and neuroprotection. (7th December 2020) - Leri, Manuela; Stefani, Massimo; Bucciantini, Monica
Abstract: Background: Autophagy, a key process involved in cell proteostasis, regulates lipid metabolism and organelle turnover and contributes to clear materials of endogenous or exogenous origin. Abnormalities in the autophagic flux may contribute to several pathophysiological conditions, associated with ageing and neurodegeneration. Alterations of the autophagy machinery are involved in the onset of Alzheimer's disease (AD), the most common form of dementia in the elderly increasingly occurring in developed countries. Indeed, several studies have revealed that the maturation of autophagolysosomes and the inhibition of their retrograde transport creates favourable conditions for accumulation of the Ab peptide whose aggregation into extracellular plaques is considered a main responsible for neuronal damage in AD. Recent data have shown that oleuropein aglycone (OleA), a polyphenol found in olive oil (EVOO), stimulates cell defences against plaque‐induced neurodegeneration and triggers autophagy. After ingestion, about 30% OleA is metabolized to hydroxytyrosol (HT), the most powerful antioxidant compound in the olive tree. Method: Accordingly, we investigated the molecular mechanism involved in autophagy activation by a mixture of OleA and HT. To this purpose, we performed a set of in vitro experiments on SH‐SY5Y cell model such as confocal microscopy;MTT assay; western‐blotting and ROS production evaluation, to extend and to deepen the knowledge on the molecular determinants of the beneficial properties of olive polyphenols. Result: Our results show that a mix of OleA/HT is able to activate the autophagy pathway more than the same amounts (in molar terms) of OleA or HT. Moreover, a reduction of ROS production with a significant recovery of cell viability was observed in cells exposed to toxic Ab1‐42 oligomers. Conclusion: These studies confirm and extend previous data and provide the rationale for consideration of these molecules as promising candidates for prevention and long‐term nutraceutical treatment of neurodegeneration or as molecular scaffolds for further pharmacological development.